Volatility and Return Spillovers Between Sukuk Markets, Green Bonds, and Conventional Markets - Gokmenoglu, Korhan K.; Joof, Foday (Springer International Publishing Ag, 2025)
Despite the recent growth in sukuk and green bond markets coupled with investors' desire for socially responsible investments, the literature is still limited. Thus, we investigate the volatility and returns spillover between socially responsible investments (sukuk, green bonds) and conventional markets (bonds, equity, and natural gas). We applied the Diebold and Yilmaz (Int J Forecast 28(1): 57-66, 2012) approach to capture the time-in-varying and time-varying spillovers from December 28, 2012, to December 13, 2022. Our empirical findings indicated low connectedness between sukuk and green bonds; however, both are net transmitters of return and volatility on average. Similarly, sukuk and green bonds exhibited high connectedness with bonds but low with the equity and fossil fuel energy markets. The time-varying results also revealed that return and volatility spillover in these markets reached their highest level during the COVID-19 episode, followed by the war in Ukraine. Furthermore, sukuk and green bonds are the net receivers of return and volatility spillovers, whereas the bond market is a net transmitter throughout the period under study. The low volatility and return spillover between sukuk and green bonds suggest a potential hedging benefit between the two assets.
8th International Conference on Banking and Finance Perspectives-ICBFP -- MAY 23-25, 2024 -- Ankara, TURKIYE
Keywords: Sukuk market; Green bonds; Volatility spillover; Return spillover